The mobile development of Malaysian local fruits learning games / Zalikha Abdul Wahid - Abdul Wahid, Zalikha (2015)
In Malaysia, there are a lot of local fruits can be found. Some of them come in seasons and some come in all year round. There are easy to get when the fruits season come and the taste is very juicy and delicious. Nowadays, children have learned about fruits but in syllabus at the school they are not focusing on local fruits in Malaysia. The children do not know which one are our local fruits. There are one method have been used to develop this application which is a survey. Survey method are divided into two categories which are interview and questionnaire. From the questionnaire conducted it can be concluded that majority of the student did not recognize which one is Malaysian local fruits. Furthermore, in this era children do not interested learning from flash card because of the extensive use of technology such as a smartphone and computer. To overcome this problem, Malaysian Local Fruits Learning Games is develop using mobile platform. Besides learning, three educational games are developed for children to learn and have fun. Combination of multimedia elements such as sound, image and text in learning makes the children more focus on what they are learning. It also will give a more positive impact to the children to know which one is a local fruits in Malaysia. This application is developed for children age six years old. Future works suggested are add more educational games into the application so user can learn and play the games to gain the knowledge.